In silico and in vitro methods to optimize the performance of experimental gastroretentive floating mini-tablets. (3rd May 2016) - Eberle, Veronika A.; Häring, Armella; Schoelkopf, Joachim; Gane, Patrick A. C.; Huwyler, Jörg; Puchkov, Maxim
Abstract: Context : Development of floating drug delivery systems (FDDS) is challenging. To facilitate this task, an evaluation method was proposed, which allows for a combined investigation of drug release and flotation. Objective : It was the aim of the study to use functionalized calcium carbonate (FCC)-based lipophilic mini-tablet formulations as a model system to design FDDS with a floating behavior characterized by no floating lag time, prolonged flotation and loss of floating capability after complete drug release. Materials and methods : Release of the model drug caffeine from the mini-tablets was assessed in vitro by a custom-built stomach model. A cellular automata-based model was used to simulate tablet dissolution. Based on the in silico data, floating forces were calculated and analyzed as a function of caffeine release. Results and discussion : Two floating behaviors were identified for mini-tablets: linear decrease of the floating force and maintaining of the floating capability until complete caffeine release. An optimal mini-tablet formulation with desired drug release time and floating behavior was developed and tested. Conclusion : A classification system for a range of varied floating behavior of FDDS was proposed. The FCC-based mini-tablets had an ideal floating behavior: duration of flotation is defined and floating capability decreases after completion of drug release.